2020
DOI: 10.1039/c9tb02375e
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired polynorepinephrine nanoparticles as an efficient vehicle for enhanced drug delivery

Abstract: Biocompatible polynorepinephrine based particles with excellent biocompatibility for efficient delivery of therapeutics to cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Notably, PDA structural properties can be tailored on specific application requirements by varying the synthetic conditions (i.e., DA concentration or buffer composition) [ 33 ]. Recently, norepinephrine (also known as noradrenaline), a neurotransmitter and vasopressor moiety, widely employed in medicine, has been proposed as a novel melanogenic precursor [ 34 , 35 ]. It undergoes oxidative polymerization forming both monodisperse nanoparticles [ 34 ] and thin coatings, with tough adhesive properties on different substrates.…”
Section: Synthetic Melanin-like Materials: Opportunities and Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, PDA structural properties can be tailored on specific application requirements by varying the synthetic conditions (i.e., DA concentration or buffer composition) [ 33 ]. Recently, norepinephrine (also known as noradrenaline), a neurotransmitter and vasopressor moiety, widely employed in medicine, has been proposed as a novel melanogenic precursor [ 34 , 35 ]. It undergoes oxidative polymerization forming both monodisperse nanoparticles [ 34 ] and thin coatings, with tough adhesive properties on different substrates.…”
Section: Synthetic Melanin-like Materials: Opportunities and Issuementioning
confidence: 99%
“…Recently, norepinephrine (also known as noradrenaline), a neurotransmitter and vasopressor moiety, widely employed in medicine, has been proposed as a novel melanogenic precursor [34,35]. It undergoes oxidative polymerization forming both monodisperse nanoparticles [34] and thin coatings, with tough adhesive properties on different substrates.…”
Section: Synthetic Melanin-like Materials: Opportunities and Issues Of Biomimetic Approachesmentioning
confidence: 99%
“…Perhaps the most famous mussel-mimetic synthetic polymer material, and coating in particular, is poly(dopamine), PDA [44,65,[128][129][130][131][132][133][134][135], stemming from the oxidative polymerisation of dopamine in aqueous alkaline solutions. Virtually any substrate dip-coated in such a solution will receive a spontaneously formed adsorbate layer from the oxidation-driven self-polymerisation of dopamine, while self-assembled dopamine aggregates will form at the same time in solution.…”
Section: Chronology Of Synthetic Mussel Protein Analogues and Mimics: Structures And Synthesis/modification Strategiesmentioning
confidence: 99%
“…An array of studies (expanding in a very wide range of possible applications) summarised in several reviews [128][129][130][131] has followed the first polydopamine account [65], in which the process parameters were varied, aiming to address some of the issues with polydopamine coatings [128,129,131]: slow coating thickness build-up and high roughness (at least for some applications), narrow pH range, incorporation of Tris HCl in the polydopamine structure (due to its amine group) and at best modest mechanical properties. For this purpose, essentially all process parameters (concentration, solvent, temperature, immersion time, amine-free buffer molecules, additional oxidant, pH, additional UV/microwave energy) have been re-visited [128][129][130][131], including dopamine itself: it has been shown rather quickly that this oxidative self-polymerisation approach is applicable to a range of catecholamines, including l-DOPA itself [132] (this polymer however, poly(DOPA), is not to be confused with linear poly(l-DOPA) presented in Scheme 8), and norepinephrine [133]. Thermal annealing of PDA coatings (at 130 • C under vacuum) has been recently proposed as a facile way to enhance their mechanical robustness [134].…”
Section: Recent Advances In Mussel-inspired Polymers As Marine Antifouling Coatingsmentioning
confidence: 99%
“…Despite a widespread study of PDA, there is a paucity of research in the utilization of polynorepinephrine (PNE) as an innovative antifouling coating. Our group recently reported on the polymerization of PNE and demonstrated that PNE nanoparticles have excellent antifouling ability against both positively and negatively charged proteins (lysozyme and bovine serum albumin (BSA), respectively) …”
Section: Introductionmentioning
confidence: 99%